Kualitas Ruang Terbuka Hijau dan Potensi Pariwisata Kreatif di Taman Indonesia Kaya, Kota Semarang - Eko Setyo Widyonarso; Fadjar Hari Mardiansjah (Borneo Engineering : Jurnal Teknik Sipil, 2020)
Along with the increasing density of the city that shifts green space, urban parks ultimately become the only place for urban communities to feel the connection to nature. Therefore, it is important to have a good quality city park. City residents' opinions about the factors that encourage visitors to visit city parks are also important as input and evaluation for city park providers. On the other hand, there is potentially given by city parks other than just as a place for recreation and relaxation. Therefore, this study wants to show how the quality of city parks, the factors which make visitors come to city parks, and what kind of potential can be achieved from city parks. This research was conducted and presented in a descriptive-qualitative form to provide a complete picture of the phenomena that occur in city parks. The results obtained are that TIK has a good quality park, able to attract visitors, and has the potential for creative tourism.